PENGEMBANGAN MEDIA KOMIK DIGITAL BERBASIS KONTEKSTUAL MATERI NILAI_NILAI PANCASILA KELAS III SD - Nabiilatudzakiyah (STKIP Subang, 2021)
The values ​​of Pancasila are very important lesson to be instilled as early as possible to students so that they become intelligent and noble generations, but the use of learning media in this material is minimal Therefore, this study aims to produce a contextual based digital comic media that is feasible and valid to be used on Pancasila values material in grade III Elementary School and can make it easier for students to understand Pancasila values so that student can be apply them in everyday life. The method used in this research is Research and Development (R&D) and uses the ADDIE model. The results of product development after validation bye expert and get the percentage of eligibility 91% form material experts and 96% from media experts. Then validated by 2 teachers and get a percentage of 96.4% eligibility. The digital comic learning media was tested for class III SDN 11 OKU. In the One to one evaluation stage, the percentage of feasibility is 92.4%, in the small group evaluation stage, the percentage of feasibility is 93.2%. Then at the Field evaluation stage, the percentage of feasibility is 86.04%, meaning that contextual-based digital comic learning media material for grade III elementary school Pancasila values ​​is very feasible for used and can make it easier for students to understand the material.